건강검진 초음파에서 지역별 간질환 유병률 비교 분석 - 이미연(Mi-Yeon Lee); 정홍량(Hong-Rayng Jung); 임청환(Chung-Hwan Lim) (한국콘텐츠학회 논문지, 9(3), 2009)
The study find out developmental factors of the liver diseases in 29,531 subject of the healthy adults who diagnosed by using ultrasound at healthcare centers located at 6 cities around the nation. The results are as follows. Based on the result of the study, the liver diseases diagnosed by using ultrasound revealed to show 43.1％ of prevalence, and the occurrence was significantly higher in male(23.3％) than in female (19.8％)(p<0.001). The disease revealed to show highest prevalence rate in regionally, Dae-jeon was found to record the highest prevalence by showing 49.6％ (p<0.001). The order of liver disease prevalence was the highest in Dae-jeon(49.6%),which was followed by Seoul(48.2%), Busan(42.9%), Incheon(36.2%), Daegu(36.2%), Kangju(32.1%)(p<0.001). The order of hepatic disease prevalence was the highest in fatty liver (69.7％), which was followed by intrahepatic cysts (13.2％), intrahepatic calcification (9.6％), intrahepatic hemangioma (4.5％), intrahepatic tumor (1.4％), diffuse liver disease (1.0％),and liver cirrhosis (0.5％) (p<0.001). The liver disease revealed to show highest prevalence rate in 40s and regionally, disease was found to record the highest prevalence from 30s to 50s (p<0.001). The distribution of the liver diseases by sex revealed to show the higher occurrence of the fatty liver and the diffuse liver diseases in male, but the intrahepatic cysts, intrahepatic calcification and intrahepatic tumors were highly distributed in female. In the regional evaluation, the fatty liver was most often found in Busan, and intrahepatic cysts, intrahepatic hemangioma, intrahepatic calcification and intrahepatic tumors were highly found in Dae-jeon and Seoul revealed to show higher occurrence of diffuse liver disease than other regions (p<0.001). The multiple regression analysis for the related factors which affect the prevalence of the liver diseases resulted to show the higher prevalence by age. sex, 전국 6개 도시의 종합검진센터에서 검진 서비스를 받은 건강한 성인 총 수진자 29,531명(서울 11,976명, 인천 3,749명, 대전 3,759명, 광주 3,155명, 대구 3,470명 부산 3,422명)을 대상으로 간질환 유병률을 분석한 결과는 다음과 같다. 간질환 유병률은 43.1％로 나타났고, 성별로는 남성에서 23.3％, 여성에서 19.8％로 남성에게서 유의하게 높게 나타났으며(p<0.001), 지역별 간질환 유병률은 대전이 49.6％로 가장 높았고, 서울 48.2％, 부산 42.9％, 인천, 대구 각각 36.2％, 광주 32.1％ 순으로 유의한 차이가 있는 것으로 나타났다(P<0.001). 간질환 유병률 순위는 지방간 69.7％으로 가장 높게 나타났으며, 간내낭종 13.2％, 간내석회화 9.6％, 간내혈관종 4.5％, 간내종양 1.4％, 미만성간질환 1.0％, 간경화 0.5％ 순으로 나타났다. 연령별 유병률은 전 간질환이 40대에서 가장 높게 나타났으며 30대에서 50대에 높은 유병률로 유의성이 있는 것으로 나타났다(p<0.001). 간질환의 지역별 유병률은 부산은 지방간, 대전은 간내낭종, 간내혈관종, 간내석회화, 간내종양, 서울은 미만성간질환이 타 지역에 비하여 높았으며 이는 통계적으로 유의성이 있는 것으로 나타났다(p<0.001). 간질환 유병률에 영향을 미치는 관련요인의 다중회귀분석 결과는 연령이 증가할수록 발병 가능성이 높게 나타났고, 연령 및 성별의 유병률에서 유의성이 있는 것으로 나타났다(p<0.05).